Long-Term Effects of an Informal Education Program on Tourist Environmental Perception - Machado Toffolo, Mariana; Simoncini, Ginevra Allegra; Marchini, Chiara; Meschini, Marta; Caroselli, Erik; Franzellitti, Silvia; Prada, Fiorella; Goffredo, Stefano (Frontiers in Marine Science, 2022)
Tourism is one of the most important economic sectors worldwide, with significant overarching impact on the environment, including negative effects caused by tourist inappropriate behavior while on vacation. By providing informal educational activities, tourism also has an educative role that leads to positive learning outcomes and beneficial environmental effects. Here we present the short- and long-term outcomes of a project for environmental education (Glocal Education) carried out in three travel destinations, aimed at promoting sustainability variables (knowledge, attitude, and awareness) in participating tourists. Since psychological components can affect learning outcomes, we also considered tourist satisfaction in participating in the project and identification with its values, as well as the intention to travel with the hosting tour operator again in the future. Tourists were asked to complete evaluation questionnaires three times: before Glocal Education activities, right after activities (i.e., while still on vacation), and after at least one year from initial project participation. Short- and long-term learning outcomes were tested, and possible relations between these variables and psychological components (satisfaction, identification, and intention) of the learning experience were verified. Overall, knowledge, attitude and awareness increased in the short term, while in the long term, knowledge and attitude decreased, and awareness remained constant. In most cases, psychological components showed positive relation with sustainability variables, which suggested their important role in structuring and carrying out environmental education activities. This study suggests that informal environmental education activities can be advantageous for tourism stakeholders in terms of customer loyalty. Such activities can contribute to enhance environment literacy, by allowing tourists to observe the environmental impact caused by human activity, and understand how their day-to-day actions, even if small, might help address some of the current concerns for environmental conservation.